Interpretation of Subsurface Structure Based on Magnetic Anomaly Analysis as Geothermal Manifestation in Lake Linting Deli Serdang - Sitompul, Yusril Padli; Sirait, Ratni; Lubis, Ridwan Yusuf (Lambung Mangkurat University Press, 2024)
ABSTRACT- Research has been carried out with the aim of determining the type of subsurface lithology of the geothermal area in Lake Linting Deli Serdang, to determine the geological structure, as well as the type of rock that functions as a reservoir for geothermal manifestations. Data processing uses geomagnetic methods with a Proton Precission Magnometer (PPM) model GEM Systems type GSM-19T, starting with IGRF corrections and daily corrections as well as qualitative and quantitative interpretation. Based on 2D modeling of subsurface lithology, the reduction cross-section model to the poles of the A-A' path is dominated by dacite rock with a susceptibility of 0.003 cgs, andesite rock has a susceptibility of 0.006 cgs, and pyroclastic rock has a susceptibility of 0.001 cgs. The reduction cross-section model to the poles of the B-B' path is dominated by pyroclastic rocks with a susceptibility of 0.001 cgs, dacite rocks with a susceptibility of 0.003 cgs, and andesite rocks with a susceptibility of 0.006 cgs. The geological structure based on the pole-reduction cross-section model of the A-A' and B-B' trajectories is characterized by a graph of ups and downs from positive magnetic intensity to negative magnetic intensity, which is estimated to be a normal fault and the rock that functions as a good reservoir is dacite rock, because Dacite rock has good porosity and permeability, so that geothermal heat can be heated and accumulated well, this is based on the fact that it has a low anomaly value with an anomaly value of -44 nT. This rock is a type of volcanic igneous rock that makes up the geothermal reservoir zone